Diversidade Genética, sistema de cruzamento e fluxo gênico em Bagassa guianensis Aubl. (Moraceae), uma espécie madeireira endêmica da Amazônia. - Arruda , Cinthya Cristina Bulhões (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
The logging of large trees in tropical forests causes a decrease in the density of reproductive individuals, which likely affects the pattern of pollen dispersal and the mating system of the remnant trees. Here, we investigate the impact of logging on the mating system, genetic diversity and gene flow of the low-density, anemophilous-insect pollinated, dioecious tree Bagassa guianensis in the Central Amazon forest using six microsatellite loci. Open-pollinated progenies were collected from 18 female trees within a 500 ha plot before logging (488 seeds) and from 10 remaining female trees after logging (232 seeds). The total number of alleles in the open-pollinated progeny was significantly higher before (71) than after logging (57). The average number of alleles per locus, allelic richness, observed and expected heterozygosity were not significantly higher before logging ( A = 11.83, 42 R = 7.91, o H = 0.626 and e H = 0.693) than after logging ( A = 9.50, 42 R = 7.20, o H = 0.676 and e H = 0.690), whereas the effective number of pollen donors was significantly higher after ( ep N = 6.6) than before logging ( ep N = 3.4), indicating that logging increases the genetic recombination. Although we observed that logging substantial reduced the effective population size of the adult population which may affect the new generations. In relation to pollen flow, our results suggest intensive pollen movement in the area and long pollen dispersal distance before and after logging. The average pollen dispersal distance was longer before (1,606 m) than after logging (1,181 m), although a similar effective neighborhood pollination area before ( ep A =292 ha) and after logging (300 ha) was found. Significant difference was observed in the patterns of pollen dispersal before and after logging, suggesting that logging changed the pollen dispersal patterns. In general the results suggest that with the large species pollen flow, the surrounding populations can compensate the putative loss of alleles due logging, since large areas of forest will be conserved.
Keywords: Bagassa guianenis; Manejo florestal; exploração de impacto reduzido